Consumer wine knowledge: components and segments. Issue 3 (20th August 2018) - Ellis, Debbie; Caruana, Albert
Abstract : Purpose: What consumers know about a product affects many aspects of their behaviour and is particularly important for marketers to understand when it comes to developing marketing strategy. The purpose of this paper is to understand the components of consumer knowledge of wine and to investigate these as a potential basis for wine market segmentation and targeting. Design/methodology/approach: A quantitative, descriptive research design is adopted. An online survey consisting of three sections, measuring objective knowledge, subjective knowledge and classificatory variables, was developed and fielded, and data were collected from US wine consumers via Amazon.com's MTurk platform. The psychometric properties of the measures used were determined, and a two-dimensional segmentation typology was developed. Findings: The study supported the positive relationship between objective and subjective wine knowledge, while the combination of the two components led to the identification of four groups of consumers titled: neophytes, snobs, modest and experts. Practical implications: In a market that is highly fragmented, consumer knowledge about wine has been shown to provide a useful basis for wine market segmentation allowing for different marketing activities to target the four groups identified. Originality/value: While other research has considered either objective or subjective knowledge on its own, this study's major contribution is the investigation of the wine consumer segments on the basis of the combination of objective and subjective consumer knowledge. A consumer knowledge type grid is developed that has implications for marketing segmentation and targeting. Implications of this new typology for future research are identified.